The Role of Teachers in Preparedness Students Level Facing Tsunami Disasters - Marlyono, Setio Galih; Wijayanto, Bayu (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
Schools in tsunami-prone areas have a very high-level disaster vulnerability. Disaster mitigation must be given adequately by the school to students in improving their preparedness, for instance in the infrastructure aspect, such as building disaster friendly schools which are completed by provision signs for disaster evacuation routes, as well as providing early warning system. Furthermore, the skill of human resources in facing disaster situation needs to be involved. In the school environment, the majority of the population was dominated by the students. It will be at high risk if the students are not aware of the tsunami disaster. Teacher factors significantly influence the increase in tsunami preparedness of students. This study explored the role of the teacher in the students' preparedness in dealing with the tsunami disaster. The research used the quantitative descriptive method. Primary and secondary data were collected using a survey. The population of the study was the teachers and the elementary, secondary, upper secondary school students in the Pangandaran District. Students' preparedness were examined by Carter, LIPI, and UNESCO parameter. Results of the research showed that the students’ preparedness score is 8,16 (highly significant) for elementary school, 5,86 (less significant) and 5,52 (less significant) consecutively for secondary and upper secondary school. The high score role of an elementary school teacher of the preparedness of the students caused by the personal closeness between teachers and students so that the student comprehend the learning materials effectively. Nevertheless, the lack of teacher attention personally to students and the lack of teacher understanding about disaster awareness, especially tsunami, were considered as the main factors that cause low students’ scores. Providing the training to the teacher about disaster preparedness, which held by the local government (Education Department), is one of the alternatives that we can do to equip the students in improving their preparedness to the tsunami.